Theater in der Irrenstalt : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in German at Massey University - Boland, Sue Mary (Massey University, 1977)
The image of the madhouse has long been used to express man's existential insecurity. Two German plays of the early sixties, Friedrich Dürrenmatt's Die Physiker (1962) and Peter Weiss' Die Verfolgung und Ermordung Jean Paul Marats dargestellt durch die Schauspielgruppe des Hospizes zu Charenton unter Anleitung des Herrn de Sade (1964) are set in the insane asylum. Although the two settings differ - the former play being set in a modern sanatorium, the latter in an infamous nineteenth-century madhouse - the use of this dramatic space in both plays is significantly similar. This thesis investigates the relationships of space and time in the dimensions of the asylum first in Die Physiker then in Marat/Sade. to discover the links of this dramatic metaphor to our reality, the way in which the audience is involved in the dramatic space of the madhouse and the contribution of this setting as a dynamic element of the drama. A network of symbolic objects, signs and leitmotivs structures the apparent confusion of the asylum in Dürrenmatt's Die Physiker, and signals its transition from a place of refuge to a prison. The protected, static atmosphere of the asylum turns out to be a trap, and withdrawal from responsibility proves irresponsible, if not impossible. The spatial development of the play is paradoxical: as the madhouse closes in on its inmates and the outside world disappears, a new breadth of perspective and vision becomes possible. The time structure similarly brings history, its inexorable chain of causality and its tyranny over the individual into focus. Past and present are taken up in the metaphor of the madhouse, which is then projected onto our future. In Weiss' Marat/Sade several levels of time and place are interwoven on the contemporary stage Weiss presents his play, which shows the presentation by the Marquis de Sade of a play, depicting events of the French Revolution, before an audience in the asylum of Charenton in 1808. Again, a somewhat menacing order is imposed on the equally menacing disorder of the madhouse. The various levels of space and time gradually draw together, trapping the spectator in an environment of brutal inhumanity and institutionalised oppression which is, in fact, as aspect of his own experience of reality. On every level of carefully structured space and on the treadmill of time, man's desire for freedom is trapped. The historical pattern of prediction and inevitable fulfilment, cause and effect, depriving man of self-direction, is projected onto our future. While offering no false solutions for the dilemma of modern man, the asylum becomes a focal point from which history and present reality can be viewed as having some kind of coherent continuity. The asylum serves as a containing form, a framework which provides structure and form to express our chaotic and disordered reality.
Content in German
Keywords: 20th century German drama; History and criticism; Mental illness in literature